ORAL CHANGES IN A GROUP OF PATIENTS WITH HIGH BLOOD PRESSURE -CLINICAL TRIAL - Dana Gabriela Bosînceanu; Cosmin Bida; Ioana Marţu; Doriana Agop Forna; Elena Raluca Baciu; Alice Arina Ciocan-Pendefunda; Dan Nicolae Bosînceanu; Carina Balcoş; Zenovia Surlari; Maria Bolat (Romanian Dental Association for Education, 2019)
Aim of the study The present study aimed to detect the existence of visible clinical effects in the oral cavity caused by hypertension and its related medication.Material and methods. The study was conducted on a group of 165 patients, 90 men and 75 women aged 20-80 years, the mean age being 53.2 years who were treataed in the Faculty of Dental Medicine in Iasi. All patients included in the study were known as hypertensive patients and were undergoing treatment with antihypertensive drugs. Xerostomia was reconfirmed using a mini questionnaire.Results.The main changes were observed in the oral bleeding and gingival hyperplasia, periodontitis, lichenoid reactions, xerostomia and paralysis of the facial nerve. Gingivitis and periodontitis were confirmed by the Russell periodontal index.Conclusions. In all types of diseases cardiovascular, specific medication has resulted in pathological manifestations in the oral cavity